Passiflora edulis: An Insight Into Current Researches on Phytochemistry and Pharmacology - Xirui He; Fei Luan; Yan Yang; Ze Wang; Zefeng Zhao; Jiacheng Fang; Min Wang; Manhua Zuo; Yongsheng Li (Frontiers in Pharmacology, 2020)
Passiflora edulis, also known as passion fruit, is widely distributed in tropical and subtropical areas of the world and becomes popular because of balanced nutrition and health benefits. Currently, more than 110 phytochemical constituents have been found and identified from the different plant parts of P. edulis in which flavonoids and triterpenoids held the biggest share. Various extracts, fruit juice and isolated compounds showed a wide range of health effects and biological activities such as antioxidant, anti-hypertensive, anti-tumor, antidiabetic, hypolipidemic activities, and so forth. Daily consumption of passion fruit at common doses is non-toxic and safe. P. edulis has great potential development and the vast future application for this economically important crop worldwide, and it is in great demand as a fresh product or a formula for food, health care products or medicines. This mini-review aims to provide systematically reorganized information on physiochemical features, nutritional benefits, biological activities, toxicity, and potential applications of leaves, stems, fruits, and peels of P. edulis.